HUBUNGAN INFEKSI NEMATODA USUS DENGAN STATUS GIZI PADA ANAK USIA 7 SAMPAI 10 TAHUN DI SDN 40 CAKRANEGARA KOTA MATARAM PROVINSI NUSA TENGGARA BARAT - I Putu Ryan Aryadana; Rusmiatik; Fahriana Azmi; I Gede Angga Adnyana (Nusantara Hasana Journal, 2023)
According to the results of the intestinal nematode infections survey in 10 provinces in Indonesia in 2014, the average national intestinal nematode infections prevalence was 30.35%. West Nusa Tenggara (NTB) is one of the provinces in Indonesia with quite high cases of intestinal nematode infections in school children with a total proportion of 69.03% and 73.45%. intestinal nematode infections in Mataram City is 87.54%. Intestinal nematode infections which cannot be treated immediately can cause a high risk of nutritional deficiencies, growth retardation, and a decreased ability to think and manage thoughts and behavior. This study was conducted to analyze the association between intestinal nematode infections with nutritional status in children aged 7 to 10 years. Observational analytic study with a cross-sectional study design was used. The sampling technique used was purposive sampling. The study was conducted in SDN 40 Cakranegara with a sample number of 38 respondents. The data obtained were analyzed by Fisher Exact Test The significance value limit was ρ-value >0.05. The characteristics of respondents were dominated by male elementary school-age children, and the highest height was 131-140 cm. with the age of most respondents aged 8 to 9 years, based on the most classes were respondents who occupied grade 2 elementary school, and with the most weight in the weight range of 20-30 kg. In bivariate analysis, it was found that there was no association between intestinal nematode infections and nutritional status, indicated by the ρ-value 0,49 (>0.05). In this study, there was no association between intestinal nematode infections and nutritional status, with a percentage of intestinal nematode infections at 5.3%, and respondents who were not infected had a prevalence of 94.7%.